Quantitative analysis of intraocular pressure and clinical-morphometric characteristics in Peters’ anomaly: a single-center study - Cronemberger, Sebastião; Veloso, Artur W.; Pereira, Maria Valeria C.; Leão de Lima, Felipe; Gonçalves da Silva, Alexandre Higino; de Figueiredo Barbosa, Luciana; Milhomens, Eduardo Gutemberg; Martins, Márcio Placedino (Frontiers in Medicine, 2025)
PurposeTo quantitatively analyze intraocular pressure (IOP) alongside clinical and morphometric findings in a cohort of children with Peters’ anomaly (PA).MethodsThis single-center retrospective study included a series of 46 children with PA. Glaucoma diagnosis in a subset was based on abnormal values of IOP, horizontal corneal diameter (HCD), or axial length (AL), individually or combined, compared to pediatric controls utilizing age-specific normative data. Patients were clinically classified into Peters I, II, III, and Peters-plus syndrome. Ultrasound biomicroscopy (UBM) was performed in 10 children.ResultsThe cohort of 46 children comprised 27 males and 19 females. All presented with central discoid corneal opacities; 33 cases were bilateral, 13 unilateral. Clinical classifications included 26 Peters I, 10 Peters II, 7 Peters III, and 3 Peters-plus syndrome. In the 29 children analyzed for biometrics, the median age at diagnosis was 7 months (IQR: 1.00–21.00). Median AL was 20.84 mm (IQR: 19.36–22.47 mm) for OD and 20.19 mm (IQR: 18.67–24.05 mm) for OS. Median HCD was 11.5 mm (IQR: 10.50–12.50 mm) for OD and 11.5 mm (IQR: 10.50–13.00 mm) for OS. Glaucoma was diagnosed in 14 patients (48.3%). A significant increase in glaucoma prevalence was observed in children >6 months old (53.6%) compared to those 0–6 months old (26.7%) (p = 0.03).ConclusionHCD and AL in PA often remain within normal limits, suggesting unique corneal biomechanics. Glaucoma in PA frequently manifests after 6 months of age, necessitating continuous monitoring.